2009
DOI: 10.1021/jm801242y
|View full text |Cite
|
Sign up to set email alerts
|

Hit to Lead Account of the Discovery of a New Class of Inhibitors of Pim Kinases and Crystallographic Studies Revealing an Unusual Kinase Binding Mode

Abstract: A series of inhibitors of Pim-2 kinase identified by high-throughput screening is described. Details of the hit validation and lead generation process and structure-activity relationship (SAR) studies are presented. Disclosure of an unconventional binding mode for 1, as revealed by X-ray crystallography using the highly homologous Pim-1 protein, is also presented, and observed binding features are shown to correlate with the Pim-2 SAR. While highly selective within the kinase family, the series shows similar p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 84 publications
(60 reference statements)
1
56
0
Order By: Relevance
“…These inhibitors include a series of pyrazine compounds (compound 9) as well as a series of isoxazolo [3,4-b]quinoline-3,4(1H,9H)-diones (compound 6). 131,132 Similar halogen hinge interactions have been reported for 4,5,6,7-tetrabromo-1H-benzimidazole, which also strongly inhibit CK2 and di-chloro-substituted β-carbolines (S Knapp, unpublished data, 2009 and pdb code: 3CXW). 133,134 An interesting aspect of many PIM inhibitors is the often observed selectivity of many inhibitors for PIM1 and PIM3 over PIM2, the latter usually being inhibited with much lower potency.…”
Section: -121supporting
confidence: 62%
“…These inhibitors include a series of pyrazine compounds (compound 9) as well as a series of isoxazolo [3,4-b]quinoline-3,4(1H,9H)-diones (compound 6). 131,132 Similar halogen hinge interactions have been reported for 4,5,6,7-tetrabromo-1H-benzimidazole, which also strongly inhibit CK2 and di-chloro-substituted β-carbolines (S Knapp, unpublished data, 2009 and pdb code: 3CXW). 133,134 An interesting aspect of many PIM inhibitors is the often observed selectivity of many inhibitors for PIM1 and PIM3 over PIM2, the latter usually being inhibited with much lower potency.…”
Section: -121supporting
confidence: 62%
“…The detailed mechanisms of the interaction among Pim family members in HCC also need further study. In view of the important roles played by Pim-2 in tumorigenesis, researches about its inhibitors grow hotter [24]. Thiazolidine congeners and isoxazole homologues are the most popular ones [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Pim-2 inhibition was more difficult to achieve than Pim-1 and Pim-3, likely due to its low K m value for ATP. 15,20 The potencies of compounds against Pim-1 kinase were influenced by several factors such as carbon chain length of the aminoalkyl group, the types of substituent at amine, and the linker between aminoalkyl group and aminopyrimidine. Compound 6c with 3-(N,N-dimethylamino)propoxy and 6h with 3-(N,Ndiethylamino)propylamino were the most potent against Pim-1 kinase.…”
Section: 15-18mentioning
confidence: 99%